MODIFIKASI ZEOLIT ALAM DENGAN SURFAKTAN HEKSADESILTRIMETILAMMONIUM KLORIDA SEBAGAI ADSORBEN ION NITRAT - Budi, Eko Setyo (Chem Info Journal, 2013)
A study on modification of natural zeolite with surfactant hexadecyltrimethyl-ammonium chloride as nitrate ion adsorbent. This study aims to modification of natural zeolite with hexadecyltrimethylammonium chloride, to test the nitrate ion adsorption on the variation of the concentration and determine the maximum adsorption capacity. The research was conducted with zeolite activation stages adding HF 1% solution for 10 minutes and dried at 120 C for 4 hours, then added a solution of 2M NH4Cl for 4 hours and dried at a temperature of 250 C for 4 hours. The next stage is active zeolite modified with HDTMA-Cl using column system with a flow rate of 0.5 mL/min. Modification characterized by FTIR spectrophotometer while the nitrate ion adsorption tests on natural zeolite and surfactant modified zeolite done using batch for 24 hours. Measuring nitrate concentrations were adsorbed by UV-Vis spectroscopy at a wavelength 220 nm. The results of FTIR spectra showed that the active zeolite modification with HDTMA-Cl has been successfully carried out with the advent of tape 1404.18 cm-1, which shows the N+(CH3)3 as well as the emergence of the tape 2854.65 cm-1 and 2924.09 cm -1 shows the range of symmetric and asymmetric CH2 of amine. Adsorption on the nitrate test also showed that the maximum capacity of the Langmuir Isotherm equation of natural zeolite at 0.502 mg/g and the surfactant modified zeolite at 5.128 mg/g.